2006 IEEE Region 5 Conference 2006
DOI: 10.1109/tpsd.2006.5507424
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of RSS-based collaborative localization methods in sensor networks

Abstract: Reliable localization is an essential building block of sensor networks. Many techniques have taken advantage of the received signal strength (RSS) measurement for location estimation in wireless sensor networks, since no special hardware implementation is required to measure RSS in almost all kinds of wireless systems. In this paper, two such techniques, MDS method and MLE that are recently proposed for collaborative location estimation, are studied in detail. From the theoretical formulation of the RSS-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…However, it is worth noting that the arrangement of the reference nodes plays a key role and it can positively/negatively affects the performance of the resulting detection accuracy whatever the algorithm at hand. As expected, the localization performances increase when the number of reference nodes grows [Latsoudas and Sidiropoulos, 2007;Li, 2007;Koneru et al, 2006]. Such an issue could represent a limiting factor for potential deployments in real-world applications.…”
Section: Received Signal Strength-based Systemssupporting
confidence: 52%
See 3 more Smart Citations
“…However, it is worth noting that the arrangement of the reference nodes plays a key role and it can positively/negatively affects the performance of the resulting detection accuracy whatever the algorithm at hand. As expected, the localization performances increase when the number of reference nodes grows [Latsoudas and Sidiropoulos, 2007;Li, 2007;Koneru et al, 2006]. Such an issue could represent a limiting factor for potential deployments in real-world applications.…”
Section: Received Signal Strength-based Systemssupporting
confidence: 52%
“…[24] As for collaborative localization in WSNs, iterative approaches based on the maximum likelihood estimator (MLE) [Li, 2007;Koneru et al, 2006;Patwari et al, 2003] or on the multidimensional scaling (MDS) method [Latsoudas and Sidiropoulos, 2007;Li, 2007;Koneru et al, 2006;Costa et al, 2006;Shang et al, 2004] have shown satisfactory tracking capabilities also in complex scenarios.…”
Section: Received Signal Strength-based Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of unknown PLE, both PLE and target location can be regarded as the parameters to be estimated. Most research works consider that the more reference nodes in the network are deployed, the more accurate estimation result gets [10], [11]. However, when there is obstruction between transmitter and receiver, the signal power can drop significantly.…”
Section: Introductionmentioning
confidence: 99%